A Study on HR Deliverables in Case Manufacturing Unit in Titan Industries with Special Reference to Watch Division, Hosur - R. Samson Samuel, B. Imran Basha , Prof. R. Veerappan, Dr. M. Raguraman, (International Journal of Scientific Research and Management (IJSRM), 2013)
Human Resource is the most significant resource in an organization. Any resource other than Human Resource has the possibilities of recovering where as Human Resource is non-recoverable one. HR Deliverables refers to the deliveries made by the HR Professionals to their employees with regard to work in an organization. The fact is how far the HR Professionals could deliver their services to their employees effectively and so shall the result be from the employees. Good employee engagement, sound communication flow system, etc is the counterpart for effective deliverables made by the HR Professionals. All these can be achieved only if the expectations of the employees are known well and deliver accordingly. This paper focuses on the expectations of the employees in various aspects and sectors in order to work effectively as a team and achieve greater heights without any communication gap between the employees and the HR Professionals. The descriptive type of research design is more suitable for this research rather from the other designs. The questionnaire consists of 5 point scaling and that identifies the strong feelings of employees.